2021
DOI: 10.3390/ijms222111494
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Dependent Effect of Silencing of TaCKX1 and TaCKX2 on Phytohormone Crosstalk and Yield-Related Traits in Wheat

Abstract: The influence of silenced TaCKX1 and TaCKX2 on coexpression of other TaCKX gene family members (GFMs), phytohormone regulation and yield-related traits was tested in awned-spike cultivar. We documented a strong feedback mechanism of regulation of TaCKX GFM expression in which silencing of TaCKX1 upregulated expression of TaCKX2 genes and vice versa. Additionally, downregulation of TaCKX2 highly upregulated the expression of TaCKX5 and TaNAC2-5A. In contrast, expression of these genes in silenced TaCKX1 was dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…Ramireddy et al ., 2021 ; and reviewed in Chen et al ., 2020a ). However, interestingly, decreased expression of CKX led to greater root mass in seedling roots of wheat and barley (Gasparis et al ., 2019 ; Jablonski et al ., 2020 , 2021a ; Zalewski et al ., 2010 ). Cytokinins are critical to cambial activity in roots (Matsumoto‐Kitano et al ., 2008 ), and the septuple AtLOG mutant showed severe retardation of root growth and defects in the RAM (Tokunaga et al ., 2012 ; Table 1 ).…”
Section: Wheat Log S Express In Multiple Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramireddy et al ., 2021 ; and reviewed in Chen et al ., 2020a ). However, interestingly, decreased expression of CKX led to greater root mass in seedling roots of wheat and barley (Gasparis et al ., 2019 ; Jablonski et al ., 2020 , 2021a ; Zalewski et al ., 2010 ). Cytokinins are critical to cambial activity in roots (Matsumoto‐Kitano et al ., 2008 ), and the septuple AtLOG mutant showed severe retardation of root growth and defects in the RAM (Tokunaga et al ., 2012 ; Table 1 ).…”
Section: Wheat Log S Express In Multiple Organsmentioning
confidence: 99%
“…Jameson and Song, 2020 ; Liu et al ., 2021 ; Nguyen et al ., 2021a ; Schwartz et al ., 2020 ; Werner et al ., 2021 ), including wheat (e.g. Beznec et al ., 2021 ; Chen et al ., 2020a , 2021a ; Jablonski et al ., 2020 , 2021a , 2021b ; Nguyen et al ., 2020 ; Ogonowska et al ., 2019 ). Historically, cytokinin biosynthesis in plants was considered a two‐step process: adenosine phosphate‐isopentenyl transferase (IPT) adding an isoprenoid side chain to an adenosine di‐ or triphosphate (ADP/ATP) to form inactive cytokinin nucleotides (Kakimoto, 2001 ; Takei et al ., 2001 ), which were then predicted to be converted by a nucleotidase to form the ribosides (Chen and Kristopeit, 1981a ), and then by a nucleosidase to form the bioactive free bases (Chen and Kristopeit, 1981b ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The observed changes suggest that the knockout of a single CKX in barley may not be sufficient to disrupt cytokinin homeostasis or increase grain yields. These authors then demonstrated that underlying mechanisms of co-regulation of the expression of TaCKX family members were similar in different spring wheat cultivars, but, depending on the content and composition of phytohormones, regulation of yield-related traits was differentially affected ( Jablonski et al, 2021 ). On the other hand, identification and characterization of all members of the CKX family, not only in E. coracana , but in closely-related species with already characterized genomes and transcriptomes ( Zhang et al, 2019a ; Zhang et al, 2019b ; Hall et al, 2021 ), may provide more information about functional features of different CKX types.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to auxin-related genes, OsNAC2 also regulates cytokinin by directly interacting with OsCKX4 , a cytokinin oxidase gene [ 57 ]. A recent study by Jablonski et al [ 58 ], reported that wheat-selected cytokinin oxidase genes ( TaCKX ) were significantly correlated with TaNAC2-5A. Furthermore, the level of expression of this gene was correlated with some yield-related traits.…”
Section: Functional Features Of Tanacsmentioning
confidence: 99%